(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Doxorubicin (DOX) therapy is associated with pulmonary toxicity and hematotoxicity as its off-target side-effects. In this study, tadalafil (TAD) was investigated for its chemopreventive potential against DOX-induced pulmonary toxicity and hematotoxicity in 48 male Wistar rats that were divided into 8 groups of 6 rats/group and orally pretreated with 2.5 mg/kg/day, 5.0 mg/kg/day, and 10 mg/kg/day TAD 1 hour before intraperitoneal injection of 2.5 mg/kg DOX on alternate days for 12 days after which the rats were humanely sacrificed. Blood samples for hematological and biochemical endpoints and lung tissue samples for oxidative stress markers, pro-inflammatory cytokines assay and for histopathology were collected. The rats body weights at the start and end of the experiments were measured. Results showed that DOX toxicity was associated with significant (p<0.0001) weight loss with corresponding significant (p<0.05) reduction in the relative lung weight. DOX intoxication was also associated with leukopenia, thrombocytopenia, lymphocytopenia, myelocytosis, and neutrophilia suggesting bone marrow suppression, while it induced significant (p<0.0001) decreases in the serum bicarbonate and pH levels, as well as an increase in iCa2+ levels. DOX intoxication was also associated with profound (p<0.0001) increases in the lung tissue oxidative stress markers. However, oral TAD pretreatment did not significantly (p>0.05) improve DOX-associated weight loss but reversed the decrease in relative lung weight. TAD pretreatments also profoundly (p<0.001, p<0.0001) reversed both the DOX-induced hematological and biochemical alterations. Overall, TAD may have potential protective effects on DOX-induced pulmonary and hematological dysfunctions, highlighting the chemopreventive potential of TAD which was probably mediated via antioxidant and/or free radical scavenging and anti-inflammatory mechanisms.